Complete mitochondrial genome sequences of two ground crickets, Dianemobius fascipes nigrofasciatus and Polionemobius taprobanensis (Orthoptera: Grylloidea: trigonidiidae) - Kohyoh Murata; Kosuke Kataoka; Ryuto Sanno; Kazuhiro Satomura; Atsushi Ogura; Toru Asahi; Kei Yura; Takeshi Suzuki (Mitochondrial DNA. Part B. Resources, 2023)
AbstractThe authors sequenced the complete mitochondrial (mt) genomes of the band-legged ground cricket (Dianemobius fascipes nigrofasciatus Matsumura, 1904) and a temperate form of the lawn ground cricket (Polionemobius taprobanensis Walker, 1869), collected in Japan. The length of the mt genome sequences was 15,354 bp in D. fascipes nigrofasciatus and 16,063 bp in P. taprobanensis. Annotation of the mt genome sequences revealed 13 protein-coding genes, two rRNA genes, and 22 tRNA genes. The orientation of the genes was the same as in other Grylloidea species, and the order was the same as in other Trigonidiidae species. In our phylogenetic analysis, D. fascipes nigrofasciatus formed a clade with D. fascipes collected in China, and the temperate form of P. taprobanensis formed a clade with P. taprobanensis collected in China. Comparison of the numbers of positions with different amino acid residues encoded by the protein-coding genes implied the separate species status of each member of each of the two pairs of ground crickets. The mt genome sequences of D. fascipes nigrofasciatus and P. taprobanensis will contribute to phylogenetic and taxonomic studies of the Trigonidiidae.